Leadership and governance of community health worker programmes at scale: a cross case analysis of provincial implementation in South Africa - Helen Schneider; Nonhlanhla Nxumalo (BMC, 2017)
Abstract Background National community health worker (CHW) programmes are returning to favour as an integral part of primary health care systems, often on the back of pre-existing community based initiatives. There are significant challenges to the integration and support of such programmes, and they require coordination and stewardship at all levels of the health system. This paper explores the leadership and governance tasks of large-scale CHW programmes at sub-national level, through the case of national reforms to South Africa's community based sector, referred to as the Ward Based Outreach Team (WBOT) strategy. Methods A cross case analysis of leadership and governance roles, drawing on three case studies of adoption and implementation of the WBOTs strategy at provincial level (Western Cape, North West and Gauteng) was conducted. The primary case studies mapped system components and assessed implementation processes and contexts. They involved teams of researchers and over 200 interviews with stakeholders from senior to frontline, document reviews and analyses of routine data. The secondary, cross case analysis specifically focused on the issues and challenges facing, and strategies adopted by provincial and district policy makers and managers, as they engaged with the new national mandate. From this key sub-national leadership and governance roles were formulated. Results Four key roles are identified and discussed: 1. Negotiating a fit between national mandates and provincial and district histories and strategies of community based services 2. Defining new organisational and accountability relationships between CHWs, local health services, communities and NGOs 3. Revising and developing new aligned and integrated planning, human resource, financing and information systems 4. Leading change by building new collective visions, mobilising political, including budgetary, support and designing implementation strategies. Conclusions This analysis, from real-life systems, adds to understanding of the processes involved in developing CHW programmes at scale, and specifically the negotiated and multilevel nature of leadership and governance in such programmes, spanning analytic, managerial, technical and political roles.